Pemanfaatan Simulator EMS untuk Meningkatkan Minat dan Kompetensi Memperbaiki Sistem Injeksi Elektronik - Nurdiyanto, Nanang (Universitas Muhammadiyah Magelang, 2018)
The purpose of this research is to increase students’ interest and competence in repairing electronic injection system through utilization of media simulator engine management system (EMS). This research uses classroom action method. Data collection techniques uses an observation to get data about students’ interest. Meanwhile, to obtain competency data in repairing electronic injection system, this research uses tests. Data analysis technique uses comparative descriptive followed by reflection. This research used 2 cycles. In the first cycle teacher used EMS simulator while in cycle II, it is developed with the intensive guidance on the group of students. Average score of students’ interest increases from 63% to 71% in cycle I and to 84% in cycle II. Meanwhile the competence score increases from 78.26 to 84. So, the use of EMS simulator media was able to increase students’ interest and competence in repairing electronic injection system.